Modelo de provisionamento de perdas de crédito em empresas do varejo - Hatamoto, Luis Otavio Pavan (2016)
This study seeks to assess whether the provision method for doubtful accounts (PDD, or 'Provisão para Devedores Duvidosos') adopted by financial institutions is applicable in retail companies and if there are adjustments needed to improve the use of these methods in this sector. Banks and other financial institutions have unique characteristics in the composition of its loan portfolio, which require the adoption of different procedures in the PDD composition against those charged by other sectors (i.e. trade, industry or services), which are free to actualize the loss provisioning. Financial companies are regulated by the Central Bank of Brazil through the Resolution of the National Monetary Council No. 2682 of December 21th 1999 which determines percentage, terms and minimum levels of classification, and which leaves the task of developing risk models for the institutions. Based on the Resolution by Central Bank of Brazil, this study evaluate the adoption of provisioning models used by financial institutions in the receivables’ portfolio from suppliers in a Brazilian retail company, and through an academic work applied to propose a model for allowance for doubtful accounts of this portfolio. The main objective is achieved due to the risk model developed fits better the provision in the losses. This benefit has two effects: first in the profits, as it reduces the expenses with allowances, and second since it smooths impacts of bad debts.